2005
DOI: 10.1007/bf03030564
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofin Planta gamma-irradiation on growth, photosynthesis, and antioxidative capacity of red pepper (Capsicum annuum L.) plants

Abstract: We investigated the effects of low-dose in planta irradiation on red pepper plants treated with gamma rays of 2, 4, 8, and 16 Gy. Growth was stimulated at 2 and 4 Gy but inhibited at 8 and 16 Gy. Photochemical quenching (qP) increased slightly in all treatment groups for 1 d after irradiation (DAI), whereas non-photochemical quenching (NPQ) decreased more noticeably. These changes in qP and NPQ were transient and had almost recovered to the control level by 2 DAI. Although carotenoid pigments also fluctuated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 39 publications
12
84
1
Order By: Relevance
“…Hormesis is the excitation, or stimulation, by small doses of any agent in any sistem (Luckey, 2003). The beneficial effect of hormesis has been well documented in species of agricultural importance (Zaka et al, 2004;Kim et al, 2005). However, there is not enough information about its use in forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Hormesis is the excitation, or stimulation, by small doses of any agent in any sistem (Luckey, 2003). The beneficial effect of hormesis has been well documented in species of agricultural importance (Zaka et al, 2004;Kim et al, 2005). However, there is not enough information about its use in forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation effects on two generations of P. sativum seedlings were studied by Zaka et al [3] reporting doses above 6 Gy significantly inhibited plant growth and productivity in the first generation while the effects were even more severe in the second generation. For red pepper plants on the other hand, Kim et al [14] reported growth stimulating effects after exposure to relatively low doses of 2 and 4 Gy, while exposure to 8 and 16 Gy inhibited growth again. As the radiosensitivity is suggested to be proportional to the size of the genome, A. thaliana, due to its relatively small genome, can probably be classified as a rather radioresistant plant species as was also suggested by Daly and Thompson [1].…”
Section: Resultsmentioning
confidence: 99%
“…This could possibly indicate that no or only little O − 2 is directly produced via energy transfer from the radiation field to molecular oxygen. As A. thaliana is probably a rather radioresistant plant, it could be possible that the radiation dose applied was insufficient to induce SOD alterations as Kim et al [14] reported an increase in SOD capacities after irradiation of red pepper plants with doses ranging from 2 to 16 Gy. (table 2) were observed for irradiated leaves and roots, important variations were observed on transcriptional level for 3 CAT isoforms in irradiated leaves.…”
Section: S404 Radioprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some low dose radiation effects in plants are not in accordance with the linear nothreshold (LNT) dose response model. It has been reported that low dose gamma radiation provokes in plants: various physiological changes on the cellular level, 6 promoted expression of specific genes, e.g., those for antioxidative defense enzymes, 10-12 hormesis, 13 cross-adaptation to UV-B irradiation, high-intensity light, and drought stress, 11,14 increased biomass yield, plant vigor and growth, and grain yield, 11,[15][16][17] fruit ripening, 18 enhancements of embryogenesis, 19 and additional trichome formation. 8 The link between PGA and low dose gamma radiation-activated redox signaling cascades is implicated by the observation that the radiation induces drastic inhibition of PGA-decomposing enzyme polygalacturonase and the upregulation of pectin methylesterase, 18 thus Figure 1.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%